Motion of Bishop Frenet Offsets of Ruled Surfaces in E3 - H. N. Abd-Ellah (Journal of Applied Mathematics)
The main goal of this paper is to study the motion of two associated ruled surfaces in Euclidean 3-space E3. In particular, the motion of Bishop Frenet offsets of ruled surfaces is investigated. Additionally, the characteristic properties for such ruled surfaces are given. Finally, an application is presented and plotted using computer aided geometric design.